Patient Perceptions and Acceptance of Routine Emergency Department HIV Testing - Brown, Jeremy (Association of Schools of Public Health, 2008)
OBJECTIVES. We report on the rates of patient acceptance and their perceptions of routine emergency department (ED) human immunodeficiency virus (HIV) testing in a high-prevalence area. METHODS. We analyzed the race/ethnicity of patients who either accepted or declined a routine HIV test that was offered to all patients in the ED of a large academic center. We also distributed a patient perception survey about ED HIV testing. RESULTS. During the study period, an HIV screening test was offered to 9,826 patients. Of these, 5,232 patients (53%) accepted the test. The acceptance rate of HIV testing was highest among African American patients (55%), followed by 52% for white, 50% for Hispanic, and 42% for Asian patients. A total of 1,519 completed surveys were returned for analysis. The most common reasons for declining a test were that patients did not perceive themselves to be at risk for HIV (49%) or they had recently been tested for HIV (18%). Overall, 84% of patients stated they would recommend to a friend to get an HIV test in the ED. When analyzed by ethnicity, 89% of African American patients stated they would recommend to a friend to get an HIV test if the friend went to the ED, but only 74% of white patients would do so. CONCLUSIONS. The Centers for Disease Control and Prevention's 2006 recommendations on HIV screening are well accepted by the target populations. Further work at explaining the risk of HIV infection to ED patients should be undertaken and may boost the acceptance rate of ED HIV screening.